The expression of epidermal growth factor receptor (EGFR) in urinary bladder carcinoma: An immunohistochemical study - Kaur, Mankirat; Khanna, Menka; Gill, Karamjit Singh; Kaur, Sukirat; Kaur, Arshdeep; Kaur, Satinder; Singh, Jaspreet; Kaur, Harwinder (Journal of Pathology of Nepal, 2025)
Background: Urinary bladder carcinoma is one of the most prevalent malignancies of the genitourinary tract. The Epidermal Growth Factor Receptor (EGFR), a transmembrane tyrosine kinase receptor, plays a crucial role in cell proliferation, differentiation, and survival. Its expression has been implicated in the pathogenesis and progression of various cancers, including bladder carcinoma.Materials and Methods: This cross-sectional study was conducted on 60 histopathologically confirmed cases of urinary bladder carcinomas diagnosed via transurethral resection of bladder tumor specimens. Immunohistochemistry for Epidermal Growth Factor Receptor was performed using a rabbit monoclonal antibody; membranous tumor‑cell staining was considered positive, and the proportion and intensity of positive cells were scored. The correlation between EGFR expression and tumor grade, stage, and other clinicopathological parameter were statistically analyzed.Results: The peak incidence of urinary bladder carcinoma was observed in the 6th  to 7th  decade of life. The majority (77%) of the patients were males. Painless hematuria was the most common presenting symptom. EGFR positivity was observed in 93% of cases. Based on histological grading, 77% of cases were high-grade, and 23% were low-grade urinary bladder carcinoma cases. A statistically significant correlation was found between the EGFR score and tumor grade (p value < 0.001) and tumor stage (p value = 0.03).Conclusion: EGFR expression was predominantly observed in high-grade and advanced-stage tumors, suggesting its association with aggressive disease and poor prognosis. Routine IHC assessment of EGFR in bladder carcinoma may provide valuable prognostic information and assist in patient risk stratification.